Bicentenario e intelectualidad - Urviola Montesinos, Luis H. (Facultad de Ciencias Jurídicas y Políticas - Universidad Nacional del Altiplano de Puno, 2022)
This paper is a sociological retrospective about the best of the republican Intelligentsia in Independence through its most representative generations: that of the 900, the Generation of the Centennial and of the 30, mainly. It is a historical interpretation that show how the impact of Inde-pendence fades over time and, despite the subsequence incessant increase of intellectuals, in any order, we no longer have references that shine with their own light like those that formed the Intelligentsia of the golden age shared by the above generations. For this analysis, the fundamental sociological concepts of generations and their succession in society are very useful, as well as their ideological contextualization in the face of the need to establish nationalism in a significantly complex and inescapable sociocultural fabric.